Recognition molecules myelin-associated glycoprotein and tenascin-C inhibit integrin-mediated adhesion of neural cells to collagen. - Bachmann, M; Conscience, J; Probstmeier, R; Carbonetto, S; Schachner, M (1995)
Because of the importance of collagens in mediating cell-substrate interactions and the association of collagens with neural recognition molecules in the peripheral nervous system, the ability of neural recognition molecules to modify the substrate properties of collagens, in particular collagen type I, for cell adhesion was determined. Two cell lines, the N2A neuroblastoma and PC12 pheochromocytoma, were investigated for their capacity to adhere to different collagen types in the absence or presence of several neural recognition molecules. Adhesion of N2A or PC12 cells and membrane vesicles from PC12 cells to collagen type I was reduced when the collagen had been preincubated prior to its application as substrate with the extracellular domain of myelin-associated glycoprotein (s-MAG) or, as control, fibroblast tenascin-C (F-tenascin). In mixture with other collagen types, s-MAG was only able to reduce the adhesiveness of collagen types III and V, but not of collagen types II and IV. F-tenascin reduced the adhesiveness of all collagen types tested. In contrast to F-tenascin, s-MAG had to be present during fibrillogenesis to exert its effect, indicating that it must be coassembled into the collagen fibril to block the binding site. Cell adhesion to collagen type I was dependent on Mg2+ or Mn2+ and inhibited by a monoclonal antibody to the alpha 1 integrin subunit. The combined observations indicate that s-MAG and F-tenascin interfere with cell binding, most probably by modifying the integrin binding site, and that the two molecules act by different mechanisms, both leading to reduction of adhesion.